Κτίρια nΖΕΒ και προσομοίωση με την χρήση του energy+ - Ιωάννου, Μυροφόρα (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The afore mentioned thesis has as its goal to turn an existing building into a “near zero energy consumption” using of the Energy+. Firstly, the geometric schematics of the building were drawn with the use of a different program (SketchUp) and then imported into the Energy+ software. The first simulation of the existing building was required in order to compare the energy consumption of this original building to that of the renovated building with the use of the energy efficient measures (EEM) which were proposed. Different simulation schemes were made taking into consideration different types of EEM such as electrical fixtures, wall insulations, coated windows and HVAC systems and an assessment was made on the different efficiencies acquired thereof. Furthermore, so as to acquire a nearly-zero energy building the need of photovoltaic solar panels was necessary. And finally, a feasibility study of the EEMs was made in order to examine if there was an economical payback on investment. Taking into consideration the above mentioned we conclude that by upgrading the existing building to a near-zero energy consumption building we can achieve a 90% reduction in its energy consumption. This can be achieved with an investment of €175000 with aits payback period being 28 years.
Keywords: Energy saving; Energy efficiency measures; Building; nZEB; Εξοικονόμηση ενέργειας; Κτίριο; Οικονομική ανάλυση